Scoping Riview: Peran Media Sosial Sebagai Sumber Pengetahuan Dalam Membangun Perilaku Keberagamaan Remaja - Andewi Suhartini; Susi Saadah; Ujang Aldi; Darojat; Erma Fitriyaa; Imas Khotimah; A.H. Eviyani Munawaroh (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to examine the role of social media in shaping adolescents' religious behavior through a literature review using  the scoping review method. Data were collected from three relevant Sinta-indexed journal articles that were selected with the focus of the study, namely the influence of social media on religious understanding, religious attitudes, and religious practices of adolescents. The results of the study show that social media, especially YouTube, Instagram, and other digital platforms, has a positive impact in the form of easy access to da'wah content, increasing religious insight, and strengthening the values of monotheism, worship, and morals. However, social media also has negative impacts such as decreased religious responsibility, weak self-control, and even deviant behavior tendencies. Factors of religious education and environmental assistance play an important role in determining the quality of social media use by adolescents. Thus, a strategy that combines comprehensive religious understanding, Islamic digital literacy, and parental and teacher assistance is needed so that social media can be used as a positive means of strengthening adolescent religiosity.